Beyond Markets and Borders: On the Community of Values Among Producers in the Bioeconomy - Pink Małgorzata (Visegrad Journal on Bioeconomy and Sustainable Development, 2025)
The first quarter of the 21st century was full of dramatic events – starting with the financial crisis in 2008, through the COVID epidemic, ending with political instability and the outbreak of war in Ukraine. In addition, the effects of global warming have intensified. The accumulation of global events of a revolutionary nature is conducive to the transformation of social values. History proves that new values are the driving force of social and economic change. The 2030 Agenda adopted by the UN indicates the need to transform the approach to production and consumption (Goal 12). This involves the dissemination of low emission approaches to production. One of these is the circular bioeconomy. The aim of this article is to diagnose the attitudes of a niche group of producers: manufacturers of bio-based materials used in construction and interior finishing. They exploit by-products of agriculture and other biomass industries and use biomass processing microorganisms. The study was based on a survey questionnaire in which entrepreneurs declared their personal values and assessed the bio-based materials market and the situation of their own company. Two research hypotheses were formulated: H1: Entrepreneurs operating in the circular bioeconomy market are characterized by a community of the values, creating ‘values archipelago’. H2: The values of entrepreneurs in the circular bioeconomy market depend on the market situation in which they find themselves and economic condition of their entity. The responses obtained were analyzed using the level of variance and Spearman‘s correlation test. As a result of the conducted analysis, hypothesis H1 was verified, while H2 was rejected. This means that in relation to the studied sample, despite the strong diversity of the environment and the situation of enterprises, entrepreneurs are characterized by very similar environmental and social values. The declared values are unrelated to the size of the enterprise, its business profile and economic condition.